EDITORIAL - Lisa McKenna; Sonia Reisenhofer (Universitas Airlangga, 2019)
Internationally, academic nurses face increasing pressure to publish their research in high quality and esteemed journals. Publication is important for disseminating research findings that can be adopted to influence the delivery of health care, but also influences rankings and prestige of universities and the professional standings of individual researchers. However, there are many challenges in making it to successful publication, particularly for novices. Internationally, journals are under growing pressure having a limited scope on how many manuscripts they can publish in any one issue and annually. As academics are under pressure to publish more, numbers of manuscripts being submitted to each journal increases every year. This means that the number rejected by each journal also increases. Many of these manuscripts may not be poorly written or present bad research, they are just not prioritised by editors as material they want to publish. It is, therefore, important to submit manuscripts that present work that an editor wants to publish in their journal. Making it through the initial editor screening can be challenging, but there are strategies that can assist with increasing the likelihood of successful publication. When developing your manuscript for publication, it is important to write specifically according to the journal you are planning to publish in. Often, researchers will write their manuscript and then try to fit it into a particular journal. This strategy may not be very successful. Journals all have different styles, audiences and manuscript guidelines. It is important when writing the manuscript to consider all of these factors. It is easy to forget you are writing for a particular audience, not just writing to get published. Researchers need to be clear about the audience who read the particular journal, and who is likely to benefit from the research outcomes being reported. It is important to carefully choose journals to publish work in and use the journal's specific author guidelines to develop the manuscript. Many papers are rejected by journal editors because they have not been developed according the actual journal guidelines. In preparing for publication, it is important that researchers identify and highlight the new knowledge that their research adds to the existing knowledge base. A lot of research conducted in nursing is very localised to a particular practice or educational setting or geographical location. Researchers need to consider the international scope of their findings if they want to publish in international journals that have readers from around the world. Such considerations need to include how research methodologies or findings could be used by others in international settings or the uniqueness or new knowledge within the paper needs to be highlighted. Overall, it is important that the manuscript is relevant to a broad, international readership as much as possible, and that this relevance is clear. There is an additional challenge for nurse researchers whose first language is not English. Most of the highly ranked journals in nursing are published in the English language. Not only are they competing for publication space, these researchers face rejection because of issues relating to English expression, grammar and tense. Collaborations with other researchers whose first language is English may be one strategy for increasing possibility of acceptance through improving the English language in manuscripts submitted to journals. Furthermore, collaborating with researchers who have established publication records means that there are members of the writing team who have expertise in being successful at navigating the many publication challenges. Ethics is also an important component in reporting on research conducted. In publishing their work, researchers are required to address ethical issues related to their studies. As editors, we often see papers where ethical considerations comprise only one statement that the research had ethical approval. However, there is more to reporting on ethics than merely acquiring ethical approval, which does not necessarily mean that the research was actually conducted in an ethical manner. In particular, it is important to discuss aspects relating to issues such as informed consent and how this was managed, as well as recruitment strategies demonstrating there was no pressure placed on potential participants or power imbalances between researcher and participants (McKenna & Gray, 2018). Overall, there is a need for more transparent reporting of ethical processes in research. The growth in predatory journals further complicates the publication process, particularly for novice researchers. Predatory journals are most often money-making scams. Each year, many good research papers are caught up in predatory journals that may not even exist, essentially becoming lost work that cannot be published anywhere else. It is very important for researchers to be aware of how to avoid losing their valuable work to these entities (Darbyshire et al., 2016). It is not uncommon to receive emails daily from so-called journals to publish with them. They often promise a quick turnaround, sometimes in a few days which is impossible for peer review to be conducted. Many have names similar to legitimate journals so you may think they are the real journal. It is very important to carefully check that a journal is legitimate before submitting any work to it. Usually, a lot of work has gone into developing a manuscript for publication and it is vital not to lose that effort. The need to publish nursing research is increasing. However, this has also increased the competition and number of manuscripts submitted to international journals each year. Being successful in publishing is complex but necessary and empowering. Researchers need to consider a range of strategies they can use to increase the possibility of successful publication in appropriate journals.